Determining the thermal stress limit of LED lamps using highly accelerated decay testing. (5th June 2016) - Cai, Miao; Yang, Daoguo; Mo, Yuezhu; Huang, Jianlin; Yin, Luqiao; Yang, Lianqiao; Chen, Xianping; Chen, Wenbin; Zhang, Guoqi
Highlights: Highly accelerated decay testing ( HADT ) for LED lamps is proposed. The abnormal thermal stress level can be analyzed with the step-fitting procedure. The thermal stress limit ( TSL ) of LED light engines is further detected by the HADT . The SSADT effectively accelerates the decay process of lamps within the achieved TSL . The proposed HADT has significant potential use in the qualification of LED lamps. Abstract: Highly accelerated decay testing ( HADT ) based on the subsystem isolation method for light-emitting diode ( LED ) lamps is proposed. The proposed test identifies the desired thermal stress limit ( TSL ) in a given humidity stress for LED light engine subsystems. In HADT, a monitoring procedure for the in situ pseudo-junction temperature ( Tpj ) of LED lamps and a step-fitting analysis procedure for the monitored parameters are suggested to detect abnormal thermal stress levels. The obtained TSL is applied to step-stress accelerated degradation testing ( SSADT ) to verify the uniform decay mechanisms at various stress levels. Results show that the goodness-of-step fit analysis of the monitored parameters effectively identifies the abnormal thermal stress levels. Consequently, the TSL of LED light engines can be clearly observed through the in situ Tpj and optical parameters monitored in HADT . The application study shows that SSADT rapidly and effectively accelerates the decay process of LED lamps, and the tested samples undergo uniform decay mechanisms at three reasonable stresses, which are selected based on the obtained TSL . The proposed HADT has significant potential use in the qualification specification of LED lamps.